Unlocking the production, bioactivity properties, and potential applications of hydrolyzed collagen from different sources: a review - Shaik, Mannur Ismail; Hiefnee, Assyarafanee; Yusri, Anis Syafiqah; Sarbon, Noraizah Mhd; Ismail-Fitry, Mohammad Rashedi; Sarbon, Norizah Mhd (Codon Publications, 2025)
Collagen plays a crucial role in maintaining the structure of different organs and tissues. In contrast, hydrolyzed collagen is a group of peptides with a low molecular weight obtained enzymatically. This review covers different methods applied for collagen extraction, the bioactivities possessed by collagen, and the potential application of hydrolyzed collagen in many sectors. Acid, alkali, and enzyme extractions are the standard methods used for collagen extraction. Still, the enzyme extraction method was the most efficient and preferred due to less waste and shortened processing time. Although advanced collagen extraction techniques, such as deep eutectic solvent extraction, supercritical fluid extraction, and microwave-assisted extraction, offer potential benefits, they currently face hurdles related to optimization, product stability, initial capital investment, and operational complexity. The hydrolyzed collagen provides good functional properties because of its bioactivities, such as antifreeze, antioxidant, antihypertensive, and anticancer properties. The applications of hydrolyzed collagen in the functional food, biomedical, and cosmetics industries are also discussed extensively. As far as the research is concerned, there still needs to be a review of various hydrolyzed collagen sources for their bioactive properties and potential applications. Therefore, the present review examines the production, bioactive properties, and potential application of hydrolyzed collagen from different sources.